Fumigating broiler hatching eggs with lysozyme product (Inovapure) to reduce eggshell microbial load. (3rd July 2018) - Li, Xujie; Anderson, Derek; Rathgeber, Bruce; McLean, Nancy; MacIsaac, Janice
ABSTRACT: Experiments were conducted to evaluate the effectiveness of a lysozyme product (InovapureTM) (LP ) against E. coli penetrating eggshells. In the first microbiological experiment, 60 agar-filled eggs were inoculated with E. coli suspension, then fumigated with distilled water, 1.5% or 3.0% LP or a quaternary ammonium product (QA ) at 0.125% for 10 min. In the second microbiological experiment, another 60 agar-filled eggs were fumigated with the same sanitizer treatments first, then inoculated with the E. coli suspension. Eggshells were candled and visual colonies were counted after 48 h incubation. An animal experiment was conducted to evaluate LP applied to the surface of 2080 broiler hatching eggs on hatching and growth performance. Hatching eggs were submerged in an E. coli suspension. After drip drying, eggs were randomly divided into four fumigation treatments, each with four subsets of 150 eggs. Fumigation treatments were the same as in the microbiological experiments. Eggs were incubated in 8 incubators (2 replicate incubators per treatment) and the broilers were grown to 33 d of age. In the microbiological experiments, inoculated eggs fumigated with 3.0% LP and 0.125% QA reduced ( P < 0.05) the total amount of E. coli to 11 cfu/egg and 10 cfu/egg, respectively. When eggs were sanitized prior to inoculation, 3.0% LP demonstrated ( P < 0.05) ongoing bactericidal action to prevent E. coli penetration. No differences in hatchability, fertility rate or egg weight loss percent were found among sanitation treatments. At hatch, body weight or the ratio of yolk sac weight to yolk-free body weight were not affected by the sanitation treatments. However, the application of sanitizers decreased ( P < 0.05) the presence of E. coli in the yolk sac of newly hatched chicks. Feed consumption, body weight and feed conversion ratio were not affected by sanitation treatments. However, average daily body weight gain was lower ( P < 0.05) following QA. Overall, 3.0% LP demonstrated acceptable activity against E. coli on eggshells, and provided ongoing bactericidal action to prevent E. coli penetration without negatively affecting growth performance.